Animated Videos and Reading Engagement in EFL Classrooms: Insights from an Islamic Senior High School Context - Prastika, Erika; Hayuningtyas, Nina (Journal of Language Intelligence and Culture, 2026)
Utilizing a qualitative case study design, this research investigated the strategic implementation, cognitive affordances, and systemic challenges of utilizing Animated Videos (AV) in reading instruction. The study engaged an English teacher and five eleventh-grade students, selected via purposive sampling. Data gathered through classroom observations and semi-structured interviews were analyzed using Miles, Huberman, and Saldana’s framework (data condensation, display, and conclusion drawing), with validity maintained through source and method triangulation. The findings reveal that a structured three-tier framework (pre-, whilst-, and post-viewing) transforms AV from mere entertainment into a vital cognitive tool. Rather than just increasing passive motivation, the visual-linguistic integration of AV enhanced language intelligence by reducing cognitive load, allowing learners to anchor abstract textual concepts in concrete situational contexts. Pedagogically, this shifted the instructional dynamic from lecture-heavy decoding to advanced guided questioning. However, systemic challenges persist in optimizing video-text alignment and managing cognitive drift during transitions. Ultimately, this study extends discussions on socio-cognitive development in language education by demonstrating how multimodal scaffolding can systematically cultivate sustained textual engagement and comprehension.